Pelatihan Pembelajaran Matematika Menggunakan Perangkat Lunak Matematika bagi Guru–Guru Matematika SMA/MA di Kabupaten Pasuruan - Syaiful Anam; Agus Widodo; Indah Yanti; Corina Karim; Fery Widhiatmoko; Mochamad Hakim Akbar Assidiq Maulana (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Pasuruan Regency has natural resources that have the potential to be developed, especially in the fields of agriculture, plantations and tourism. In an effort to improve the quality of human resources, improving the level of education is an important thing to do. One way to increase the number of people's participation in education is to improve the quality of learning so that people are interested in taking higher education levels. Learning media with mathematics software is expected to be able to visualize abstract mathematical objects so that it can improve students' understanding and encourage student learning motivation. GeoGebra is a mathematical software to visualize abstract mathematical objects quickly and accurately and can be used as a tool to construct mathematical concepts. One of the objectives of this activity is to improve the ability and skills of mathematics teachers in SMA/MA in Pasuruan Regency in developing mathematics learning media with GeoGebra software to visualize abstract mathematical objects (geometry objects). In addition, to improve the ability and skills of mathematics teachers in SMA/MA in Pasuruan Regency in explaining mathematical material containing geometric objects by utilizing Geogebra. The results of the training showed that the ability and skills of SMA/MA teachers in Pasuruan Regency increased significantly in the development of teaching media and in explaining geometric objects by using Geogebra.